2003
DOI: 10.1128/mcb.23.24.9283-9292.2003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methyltransferase for Modified Uridine Residues at the Wobble Position of tRNA

Abstract: We have identified a novel tRNA methyltransferase in Saccharomyces cerevisiae that we designate Trm9. This enzyme, the product of theYML014w gene, catalyzes the esterification of modified uridine nucleotides, resulting in the formation of 5-methylcarbonylmethyluridine in tRNA Arg3 and 5-methylcarbonylmethyl-2-thiouridine in tRNA Glu . In intact yeast cells, disruption of the TRM9 gene results in the complete loss of these modified wobble bases and increased sensitivity at 37°C to paromomycin, a translational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
174
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(186 citation statements)
references
References 62 publications
11
174
1
Order By: Relevance
“…17 Inactivation of the other S. cerevisiae Elongator genes encoding Elp1-Elp2p and Elp4-Elp6p displayed identical phenotypes as the elp3 null mutant including the tRNA modification defect. 17,18 This observation suggested that the Elongator complex is required for synthesis of the first step, an intermediate likely to be 5-carboxymethyluridine (cm 5 U) [19][20][21][22][23] , in formation of mcm 5 U, mcm 5 s 2 U, ncm 5 U and ncm 5 U m at U 34 in tRNA (Fig. 1).…”
Section: 15mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Inactivation of the other S. cerevisiae Elongator genes encoding Elp1-Elp2p and Elp4-Elp6p displayed identical phenotypes as the elp3 null mutant including the tRNA modification defect. 17,18 This observation suggested that the Elongator complex is required for synthesis of the first step, an intermediate likely to be 5-carboxymethyluridine (cm 5 U) [19][20][21][22][23] , in formation of mcm 5 U, mcm 5 s 2 U, ncm 5 U and ncm 5 U m at U 34 in tRNA (Fig. 1).…”
Section: 15mentioning
confidence: 99%
“…2). [20][21][22][23]52,53 Other than being a subunit required for Trm9p activity, Trm112p is also a subunit required for the activity of 3 other methyltransferases, the tRNA methyltransferase Trm11p forming m 2 G 10 in tRNA, the ribosomal methyl transferase Bud23p methylating G1575 in 18S rRNA 54 and Mtq2p methylating the release factor eRF1.…”
mentioning
confidence: 99%
“…In regard to tRNA modifications, their functions include: stability and flexibility of the tRNA structure (Motorin and Helm 2010), translational fidelity via codon-anticodon interaction (Saint-Léger and Ribas de Pouplana 2015), reading frame maintenance (Waas et al 2007;Delaunay et al 2016;Klassen et al 2016a), tRNA discrimination , nonsense suppression (Benko et al 2000), tRNA stability (Alexandrov et al 2006;Kotelawala et al 2008;Dewe et al 2012), proteome integrity (Nedialkova and Leidel 2015), sensitivity to aminoglycoside antibiotics acting at the decoding site of ribosomes (Kalhor and Clarke 2003), response to stress (Kamenski et al 2007;Chan et al 2012;Gu et al 2014), and recognition of tRNA as either self or nonself by TLR7 receptor (Kaiser et al 2014;Rimbach et al 2015). For general reviews, see Helm (2011), Hopper (2013) and Phizicky and Hopper (2015).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…Likewise, the absence of pseudouridine (c) at tRNA Tyr position 35 or m 5 C 34 in tRNA Leu CAA causes defects in tRNA-mediated nonsense suppression (Johnson and Abelson 1983;Strobel and Abelson 1986). Alterations of other modifications at position 34 such as ncm 5 Um 34 result in sensitivity to the aminoglycoside antibiotic paromomycin that causes misreading of near cognate codons (Kalhor and Clarke 2003). Some of the subunits of the enzyme responsible for ncm 5 Um 34 and ncm 5 s 2 U 34 modification were previously identified as components of the elongator complex that functions in transcriptional elongation, silencing at telomeres, and DNA damage response; it since has been shown that the phenotypes are indirect consequences of wobble position errors in translation of proteins that function in these processes (Chen et al 2011).…”
Section: Removal Of 59 Leader and 39 Trailer Sequences From Pre-trnasmentioning
confidence: 99%